(untitled) (Rassegna di Diritto, Legislazione e Medicina Legale Veterinaria, 2018)
The Authors analyze the bovine Paratuberculosis, in order to clinically classify the disease and examine the European Union’s and the Italian’s animal health law in relation to the cost-benefit costs of the eradication programmes. Bovine Paratuberculosis is a not notifiable disease neither in Italy nor in EU, according with Regulation n. 429/2016